FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PENGEMUDI BUS RAPID TRANSIT (BRT) KORIDOR II KOTA SEMARANG - Muchammad Bachrul Ulum; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Occupational stress describes the physical, mental, and emotional reaction of worker who perceive that their work demands exceed their abilities and their resource to do the work. The research aims to analyze the related factors of occupational stress on Bus Rapid Transit (BRT) Drivers performance in Semarang. The design of research conducted in this research is the explanatory research using cross sectional approach. The data was collated by using GHQ-12 questionnaire technique which arranged baseds on theoretically study. Driver at Bus Rapid Transit (BRT) corridor II in Semarang with the total 37 drivers as a respondent. The result of research showed that there was correlation between personality (ρ=0,006) and individual role in organization (ρ=0,002) through occupational stress, but there was no correlation between age (ρ=0,485), work period (ρ=0,505) and job relationship (ρ=0,851) through occupational stress. The future, Bus Rapid Transit (BRT) management should have provide socialization of hazard risk in work and the transparency of decision making in problem solving.